Laparoscopic nephroureterectomy for upper tract urothelial carcinoma – Update - Lin, Victor C. (Asian J Urol, 2016)
Upper urinary tract urothelial carcinomas (UTUCs) are uncommon and account for only 5%–10% of urothelial carcinomas. Pyelocaliceal tumors are about twice as common as ureteral tumors. Sixty percent of UTUCs are invasive at diagnosis. Radical nephroureterectomy, including the excision of the distal ureter and bladder cuff is standard of care for treatment of localized UTUCs, because of the high potential for recurrence, multifocality, and progression. Since first laparoscopic nephroureterectomy (LNU) was introduced by Clayman et al. in 1991 and improvement of laparoscopic technique and equipment, LNU has been reported to be equivalent to conventional open method. We reviewed the current literature of patients with UTUCs treated by LNU focusing on technical aspects, peri-operative and oncological outcomes. Laparoscopic radical nephroureterectomy offers the advantages of minimally invasive surgery without deteriorating the oncological outcome for treatment of UTUCs. Indications tend to increase as operator skills increase. Indications for laparoscopic or open nephroureterectomy are in principle the same. The basic requirement for laparoscopic surgery in UTUCs is to achieve benefits of minimal invasive surgery and maintain oncologic principles.